2019
DOI: 10.3389/fenrg.2018.00142
|View full text |Cite
|
Sign up to set email alerts
|

Wasting Democracy, Fueling Dissent: Refuse-Derived Fuels in Can Sant Joan (Catalonia)

Abstract: The cement industry is one of the most energy intensive in the world, contributing significantly to global greenhouse gas emissions. The use of refuse-derived fuels (RDF) in cement kilns is increasingly portrayed as a sustainable solution to reduce emissions while dealing with different types of waste. Nevertheless, the use of RDF in cement plants is contested by communities around the world, who are facing immediate environmental impacts. In this article, we examine the burgeoning movement against waste incin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…The review of the literature suggested that titles that address the interplay between energy democracy and justice can be roughly organised into three trends: conceptual papers (for instance, [4,16,20,22]), critical papers (for instance, [15,34]) or, more often, empirical studies (for instance, [1,9,23,[35][36][37][38][39][40]). With some exceptions, authors are from North America and Europe and most of the empirical analysis concerns case studies focused on these two regions, confirming the fragmentation between the Global North and the Global South.…”
Section: Method Approach and Research Designmentioning
confidence: 99%
“…The review of the literature suggested that titles that address the interplay between energy democracy and justice can be roughly organised into three trends: conceptual papers (for instance, [4,16,20,22]), critical papers (for instance, [15,34]) or, more often, empirical studies (for instance, [1,9,23,[35][36][37][38][39][40]). With some exceptions, authors are from North America and Europe and most of the empirical analysis concerns case studies focused on these two regions, confirming the fragmentation between the Global North and the Global South.…”
Section: Method Approach and Research Designmentioning
confidence: 99%